2020
DOI: 10.1016/j.annonc.2020.08.1951
|View full text |Cite
|
Sign up to set email alerts
|

1445P CS1001, an anti-PD-L1 antibody, combined with standard of care (SOC) chemotherapy for first line (1L) advanced GC/GEJ and ESCC: Preliminary results from 2 phase Ib cohorts of CS1001-101 study

Abstract: Background: CS1001-101 is an open label, multi-center study to evaluate the efficacy and safety of CS1001, an anti-PD-L1 mAb, as mono or combo therapy in patients (pts) with solid tumors or lymphomas. CS1001+XELOX regimen for 1L GC/GEJ and CS1001+CF regimen for 1L ESCC pts were evaluated in this study and preliminary results are reported herein. abstracts Annals of Oncology Volume 31 -Issue S4 -2020 S909

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…The treatment-emergent adverse events reported in this study were consistent with the safety profile of sugemalimab 13 , 14 , 16 , 17 and other immune checkpoint inhibitors in similar patients. 18 - 20 Treatment-related adverse events were manageable as most of them were grade 1-2 in severity.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The treatment-emergent adverse events reported in this study were consistent with the safety profile of sugemalimab 13 , 14 , 16 , 17 and other immune checkpoint inhibitors in similar patients. 18 - 20 Treatment-related adverse events were manageable as most of them were grade 1-2 in severity.…”
Section: Discussionsupporting
confidence: 81%
“…Our safety findings were consistent with the expected safety profile of this drug class and with previous reports of sugemalimab in advanced non-smallcell lung cancer and other solid tumors. 13,14,16,17 In this study, the majority of responding patients achieved complete response, and although cross-trial comparison is difficult and should be interpreted with caution, this was numerically higher than the reported data from other PD-1/PD-L1 inhibitors. [18][19][20] Moreover, achieving complete response, instead of partial response, has been closely correlated with longer survival in ENKTL.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Immune checkpoint inhibitors that target programmed cell death protein 1 (PD-1) or programmed cell death ligand 1 (PD-L1) have shown promising survival benefits and manageable safety in first-line treatment of patients with G/GEJ cancers in the CheckMate-649 10 , GEMSTONE-101 11 , and ORIENT-16 trials 12 . By binding to PD-1, activating antigen-specific T cells, and reversing the immune evasion of cancer, immunotherapy may be more effective in the early stages of G/GEJ cancers when the tumor is still present after the approach known as neoadjuvant therapy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In China, guidelines list nivolumab plus XELOX/FOLFOX the preferred regimen for PD-L1-positive AGC ( 9 ). Additionally, in China, many newly developed domestic ICIs are used in clinical trials for first-line treatment of AGC, such as ORIENT-16 ( 10 ), CS1001-101 ( 11 ) and SHR1210 ( 12 ). The above research results have confirmed the exact efficacy of paclitaxel plus ICIs in the therapy of AGC.…”
Section: Introductionmentioning
confidence: 99%